2022
DOI: 10.3389/fmed.2022.899821
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Diabetes Mellitus and the Risk of Latent Tuberculosis Infection: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe estimated global latent tuberculosis infection (LTBI) burden indicates a large reservoir of population at risk of developing active tuberculosis (TB). Previous studies suggested diabetes mellitus (DM) might associate with LTBI, though still controversial. We aimed to systematically assess the association between DM and LTBI.MethodsWe searched PubMed, Embase, Cochrane Library and Web of Science. Observational studies reporting the number of LTBI and non-LTBI individuals with and without DM were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
2
8
0
1
Order By: Relevance
“…Diabetes was associated with an increased prevalence of LTBI in prior studies ( Barron et al., 2018 ). A previous systematic review and meta-analysis showed that diabetes was associated with a small increased risk of LTBI ( Lee et al., 2017 ), but a recent meta-analysis showed that the risk of LTBI was found to be a 60% increased risk in persons with diabetes and a 36% increased risk in prediabetes when compared with normoglycemia people ( Liu et al., 2022 ). In addition, there were studies indicating the increased risk of incident diabetes among individuals with LTBI ( Magee et al., 2022 ), demonstrating that the LTBI population was a vulnerable group of people who were susceptible to diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes was associated with an increased prevalence of LTBI in prior studies ( Barron et al., 2018 ). A previous systematic review and meta-analysis showed that diabetes was associated with a small increased risk of LTBI ( Lee et al., 2017 ), but a recent meta-analysis showed that the risk of LTBI was found to be a 60% increased risk in persons with diabetes and a 36% increased risk in prediabetes when compared with normoglycemia people ( Liu et al., 2022 ). In addition, there were studies indicating the increased risk of incident diabetes among individuals with LTBI ( Magee et al., 2022 ), demonstrating that the LTBI population was a vulnerable group of people who were susceptible to diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A large cross-sectional study of the US national data also reported that T2DM significantly increases LTBI risk (adjusted odds ratio: 1.90, 95% confidence interval: 1.15–3.14) ( 37 ). Correspondingly, a systematic review involving 20 studies also reported a significant LTBI risk by T2DM (for cohort studies, relative risk: 1.62, 95% confidence interval: 1.02–2.56; for cross-sectional studies, odds ratio: 1.55, 95% confidence interval: 1.30–1.84) ( 38 ). The association between T2DM and ATB has been well established ( 41 ), with T2DM increasing the risk for ATB development by greater than 3-fold ( 42 ).…”
Section: Epidemiological Effects Of T2dm On Tbmentioning
confidence: 99%
“…2 Epidemiological effects of T2DM on TB 2.1 T2DM increases the risk of LTBI and ATB T2DM has been reported as a primary Mtb infection risk factor (37,38). Patients with T2DM (43.4%) and pre-diabetes (39.1%) had significantly more LTBI than those without T2DM (25.9%), with a strong association between T2DM and LTBI (adjusted odds ratio: 2.3, 95% confidence interval: 1.2-4.5) (39).…”
Section: Epidemiology and Pathogenesis Of Tuberculosismentioning
confidence: 99%
“…In a meta-analysis published in 2017, DM was associated with a small but significant risk for LTBI ( 9 ). Another more recent meta-analysis concluded that DM increased the risk for LTBI by 60% ( 18 ). Finally, more recent comprehensive longitudinal data indicate that LTBI is associated with increased diabetes incidence (hazard ratio of 1.4) in US Veterans ( 19 ).…”
Section: Introductionmentioning
confidence: 99%